Improving Studentsâ Reading Comprehension in Recount Text through Reciprocal teaching technique: A Classroom Action Research at the Eighth Grade Students of Junior High School in Pontianak in the Academic Year 2014/2015 - Rosalia, Uray (IKIP-PGRI Pontianak, 2015)
The purpose of the classroom action research is to find out the effectiveness of reciprocal teaching technique to improve the studentsâ reading comprehension. The participants of this research were 35 students of the eighth grade, class VIII-A at junior high school in Pontianak. The participants were chosen through purposive sampling, class eight was selected because they had had problem in reading comprehension since they were in grade seven. The data collecting technique of this research includes observation checklist and field note. They were covered in observation technique while reading test was covered in measurement technique. The findings showed that the studentsâ understanding in reading comprehension improved and this was proven by the result of reading test from each cycle, the first cycle mean score was 52.57, second cycle was 63.14, and the third cycle was 71.71. The last cycle means score was categorized as good. The improvements in students understanding indicates that reciprocal teaching technique is effective and applicable when it deals with studentsâ problem in reading recount text. For the teachers, this teaching technique can be a good alternative when they encounter problems in teaching reading.